PROBLEMATIKA DAKWAH DALAM MENINGKATKAN PERILAKU KEAGAMAAN - Suriati Suriati (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2014)
Schools are not only as the basis of education, but also the basis of da’wah, which is intended to create students who are islamic in their behaviour and lifes. The current reality shows that a lot of children are involved in a variety of delinquency, and the most horrible of them is free sex and drugs. This paper deals with da’wah that was carried out in Senior High School (SMA) 6 Palu and its barriers. This research shows that da’wah in this school was conducted anually, especially in Islamic holidays and the holy month of Ramadhan. Besides, da’wah was carried out in a partial and personal way. “Partial” means da’wah depends on the teachers of Islamic religious education, while “personal” means it is only desiring teachers who conduct Islamic da’wah. Moreover, the problems of da’wah in this school comprise the absence of school policy that binds all elements of school to do da’wah, in addition to the lack of budget to support the da’wah activities.